Acquisition and Processing of GPS signals based on Software Defined Radio - Lucas Castillo Delacroix; Mariano Fagre; Isidoro Vaquila; Miguel Angel Cabrera (Revista Elektrón, 2024)
This paper presents the development of a software tool that implements an acquisition block for GPS signals using SDR technology, specifically devices like the HackRF One and RTL-SDR. The tool, implemented  in Python, successfully detects satellites and estimates their parameters, offering customizable algorithm settings and the capability to visualize the satellite search space in three dimensions. Comparative tests with the GNSS-SDR software tool demonstrated excellent performance, providing a solid foundation for further development toward a complete SDR-based GNSS receiver. This work highlights the potential of SDR platforms for research and development, emphasizing their flexibility, potential for future upgrades, and cost-effectiveness in advancing future GNSS technologies.